Do Sustainability Standards Provide Environmental, Social and Economic Benefits for Independent Oil Palm Smallholders? - Aditya Nugraha; Morteza Muthahhari; Pamela; Adi Suyatno; Nurliza (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
There is much inconclusive and unclear literature on understanding the benefits of environmental, social, and economic for the sustainability standards compliance of smallholders. The study aims to build a simultaneous relationship of the sustainable standard in the context of Indonesian Sustainable Palm Oil toward the benefit of sustainable dimensions using the concept of sustainable development, incentive theory, and the concept of agricultural extension of 150 independent smallholders. The results prove that farmers' organization is the most significant, followed by management of environmental monitoring and sustainable business development. However, legal is insignificant because of thought of as a nice to have. There is limited involvement in practical communities’ instruments so agricultural extension becomes an effort to reconstruct thoughts and actions to promote sustainability, especially social sustainability. Most indicators of sustainable standards toward the benefit of sustainable dimensions indicators are poor, except for fire prevention and control which had a moderately positive effect on the conservation of biodiversity. Thus, an integrated approach to area-based risks management, local institutions with religious and traditional leaders, Community-Based-Fire-Management, conservation area buffer zone, public-private partnerships, enabling conditions to access finance, and resource distribution with budgets and geographic proximity can be an effort to encourage compliance with sustainable standards.